Internalisasi Nilai-Nilai Karakter Bangsa melalui Pendidikan Agama Islam - Lucky Damara Yusuf; Firdausih; Moh. Isbir (LPPM STAI Ihyaul Ulum Gresik, 2024)
Moral decadence is a phenomenon that is no longer uncommon in Indonesia, especially when it concerns teenagers. Starting from brawls between students, attacks, robberies, bullying, drunkenness, mass cheating, prostitution, free sex, abortion, to the brutality of motorbike gangs and much more. Seeing this, all parties, including the government, parents, society, educators and stakeholders, have a big obligation to overcome this problem. NU Tanggarang Bondowoso Vocational School is an educational institution that teaches knowledge and skills in implementing the values ​​of national moderation with students who adhere to different beliefs, some even adhere to non-Islamic religions. NU Tanggarang Bondowoso Vocational School is an educational institution under an Islamic foundation, but in learning Islamic Religious Education it has habits that do not exist in other Islamic Religious Education schools.